(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Creativity and organizational innovation is one of the most crucial issues in the business administration and is one of the factors which affects the productivity. On the other hand, the results of the international reports demonstrate a lack of creativity and innovation in the country and consequently, in Iranian organizations, which reveals the necessity for paying more attention to this issue. The purpose of this research is designing a model which consists of factors which affect the organizational innovation and creativity as well as the discovery of structural relationships between those factorsand it is achieved by using a descriptive-survey research method. The statistical population of the present study includes all employees of the Iranian government institutionsand 384 individuals were reviewed by using Cochran formula and stratified random sampling.Research tool included the creativity and innovation questionnaire of the staff from the Ran sip’s creativity Scale (1979). The validity of the questionnaires was confirmed by using the item analysis and its reliability was calculated by using Cronbach’s alpha method. Moreover, the reliability for the creativity questionnaire was 0.81 and it was 0.80 for the employees’ creativity. The designed model contains 11 factors of trust, optimism, job satisfaction, economic and job security, obvious and common job goals, organizational commitment, organizational learning, feeling justice, honesty and interest in the job and considering it as a meaningful activity, which is categorized in 8 floor levels. Findings demonstrate that among all these factors, the factor of specific and common job goals has been identified as an underlying factor in the formation of creativity and organizational innovation of employees, which has led to a sense of justice in the structure and consequently, it will lead to honesty, economic security, job security and optimism.